Fitting test of two-parameter BS fatigue life distribution and approximate interval estimation of environmental factor - WANG Ronghua (Journal of Shanghai Normal University (Natural Sciences), 2019)
Two-parameter Birnbaum-Saunders (BS) fatigue life distribution is an important failure model in the probability physical methods.It is more suitable for describing the life rules of fatigue failure products than common life distributions such as Weibull distribution and Lognormal distribution.Besides,it is mainly applied to analytical research about fatigue failure and degradation failure of electronic product performance.Based on the full sample,the test statistics are constructed for fitting test of two-parameter Birnbaum-Saunders fatigue life distribution by using the property of logarithmic moment estimation of scale parameter proposed in XU's reseaching.Three examples are given to illustrate the application of fitting test method.Besides,two new methods of approximate interval estimation of environmental factor are given for two-parameter BS fatigue life distribution,which is compared with the original method through Monte Carlo simulations.We find that the advantage of logarithmic normal approximate method is obvious,and the example is given to illustrate the application of the method.